Changes of microelement homeostasis when modeling HIPEC with cisplatine - E. D. Pykhtieieva; A. I. Gozhenko; E. G. Pykhtieieva; D. V. Bolshoy; A. M. Tretyakov (Kazimierz Wielki University, 2019)
HIPEC was simulated on laboratory rats using cisplatin (CP) at a dose of 4 mg/kg. It has been shown that perfusion of a hot and cold solution of CP changes the accumulation of platinum and the concentration of heavy metals in organs (liver, kidney, spleen, blood) in different ways. An acute HIPEC simulation experiment shows that in a fairly short exposure time, critical absorption of platinum into the blood from the abdominal cavity does not occur, although the concentration of platinum in the blood is still growing. At the same time, Pt was found on the surface of parenchymal organs and the peritoneum of rats after the end of the experiment. This platinum is closely related to the surface and is not removed during the washing process. This suggests that the general toxic effect of platinum is less pronounced and delayed than with intravenous administration, but it will certainly occur through further interorgan redistribution.